Characterisation and cross-species utility of 20 microsatellite markers for population and forensic applications in the endangered Carnaby’s Black-cockatoo, Calyptorhynchus latirostris - White, Nicole; Mawson, P.; Dawson, R.; Bunce, Michael; Spencer, P. (Springer, 2009)
We characterise 20 microsatellite loci identifiedfrom the endangered Carnaby’s Black-cockatoo(Calyptorhynchus latirostris). The primers were testedacross 40 individuals from the southwest of WesternAustralia and displayed between 4 and 11 alleles per locuswith expected heterozygosities ranging from 53 to 87% andexclusion probabilities of C0.999. These loci will be usefulin population genetic studies to facilitate conservationmanagement decisions in addition to wildlife enforcementapplications for the endangered Carnaby’s Black-cockatoo.We also tested the markers in 12 high profile and smuggledspecies from five genera, Cacatua, Callocephalon, Calyptorhynchus,Nymphicus and Probosciger. These speciesdetected between 2 and 19 alleles per locus with 50–100%amplification success.